2018
DOI: 10.1149/2.0151812jes
|View full text |Cite
|
Sign up to set email alerts
|

A Nanopipette Platform for Delivering Nanoliter Volumes of Acetylcholine

Abstract: Delivery of nano-liter volumes of neurotransmitter is important in fundamental studies to understand the brain function, as well as in pharmacological intervention for the treatment of neurological disorders. We present here a nanopipette based electrochemical delivery platform for the delivery of acetylcholine, and the measurement of the delivered acetylcholine concentration profile following its delivery. The delivery was enabled by the applied voltage and nano-liter volumes (1.342 ± 0.417 nL) of acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…88,89 One of these recent studies was carried out by McAllister and co-workers to not only deliver acetylcholine (ACh) but also measure its amount. 90 The fluorescence measurement of the ejected solution consisting of ACh and [Ru(bpy) 3 ] 2+ dye demonstrated that the average delivery volume was 1.342 ± 0.417 nl at 9 V applied potential. Relationship with applied voltage duration with increased Ach delivery was established which could be used for a more precise delivery response.…”
Section: Applications Of Nanopipettesmentioning
confidence: 98%
“…88,89 One of these recent studies was carried out by McAllister and co-workers to not only deliver acetylcholine (ACh) but also measure its amount. 90 The fluorescence measurement of the ejected solution consisting of ACh and [Ru(bpy) 3 ] 2+ dye demonstrated that the average delivery volume was 1.342 ± 0.417 nl at 9 V applied potential. Relationship with applied voltage duration with increased Ach delivery was established which could be used for a more precise delivery response.…”
Section: Applications Of Nanopipettesmentioning
confidence: 98%
“…Recently, synthetic nanopores are gaining much attention because of their implementation for the miniaturization of biosensing devices in the field of bio/nanotechnology [1][2][3]. Moreover, the nanoporous membranes are frequently employed for molecular separation and purification processes as well as energy conversion systems [4][5][6][7][8][9][10]. Depending on the desired application, the nanopore dimensions such as size, shape, surface properties as well as the utilized membrane materials can be tuned to fulfill specific requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The pore diameter can be tuned by varying the etchant concentration, temperature and the duration of the etching process. Moreover, several parameters have been adjusted such as exposure to UV light, variation of potential across the membrane and also addition of surfactants and different solvents in the etching solution to enhance the homogeneity and etching rate [7,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Various routes and methods have been explored so far for the fabrication of synthetic nanopores including ion beam sculpting, 27,28 electron beam sculpting, 29 thermal annealing, 30 micromolding, 31 dielectric breakdown, 32 laser assisted pulling of capillaries 33 and track-etching 34 in versatile materials like silicon nitride, 35 aluminium oxide, 36 boron nitride, 37 graphene, 38 polymers, [39][40][41] quartz 42 and silicon oxide. 43 Track-etching process is especially of interest for us since it allows the fabrication of different nanopore geometries by simply adjusting experimental conditions.…”
mentioning
confidence: 99%